The trouble up north - Mulhauser, Travis, 1976- (Grand Central Publishing, 2025)
"An atmospheric, haunting novel about a family of bootleggers, their troubled history, and the land that binds them. The Sawbrooks have lived on prime real estate on the lakes of Michigan since before there was prime real estate. A family of smugglers and bootleggers, every man, woman, and child in each generation has been taught to navigate the nooks and crannies of the rivers and highways that flow in and out of Canada. The hidden routes are the family's legacy. But today, the Sawbrooks are deeply fractured, and the money that's sustained the family is running out. Edward, the Sawbrook patriarch, is dying from cancer, and his wife, Rhoda, is bitterly disappointed in her three adult children. The eldest daughter, Lucy, is now a park ranger, working to federally protect the land against her mother's will; the middle son, Buckner, hasn't been the same since he came back from the army suffering from alcoholism; and the youngest daughter, Jewell, is wasting her potential as a card player and bartender. When Jewell is asked to commit a crime for a major insurance payout, she agrees, eager for the cash, but too late, she realizes that that the boat she torched wasn't empty... Together, the Sawbrooks will have to contend with the old, familial ways and the new, shifting world, and face each other-and their pain-filled past-to smuggle one more thing through and out of their land to safety"--